ANALISIS PENGGUNAAN E-FILING UNTUK PENINGKATAN KEPATUHAN WAJIB PAJAK - , Destari Nurlaila Damanik (JURNAL PERPAJAKAN, 2020)
The Directorate General of Taxes has made various new innovations in the field of taxation, namely by the use of technology and information so as to create computer applications in the tax administration system such as e-Filing to facilitate taxpayers in reporting their tax obligations. This study aims to determine the level of use of e-Filing, the level of compliance of taxpayers namely the timeliness of reporting taxes using e-Filing. The object of research was carried out at the Directorate General of Taxes. The method used is descriptive qualitative method. This study uses data collection techniques namely observation and documentation. The results showed that the number of SPT receipts through e-filing was still far from the number of registered taxpayers, so although the results of the percentage of SPT submissions via e-filing were good, but looking at the number of registered taxpayers could still be increased to achieve maximumresults . The non-maximum number of SPT submissions through e-filing shows that many compulsory compliance is still lacking, because the number of SPT submissions through e-filing can reflect how the actual tax compliance, can be seen from the target set by the Directorate General of Taxes, namely 55.00%.